Pelatihan Pembuatan Reed Diffuser Berbasis Limbah Kulit Jeruk untuk Mendukung Ekonomi Sirkular di SMK Astra Mitra Purwodadi - Bagas ardiyantoro; Anita dwi setiarini; Netty Dea Sosiantini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Orange peel waste, which is often discarded and causes environmental problems, actually has great potential for reuse. Orange peels contain essential oils that can be processed into reed diffusers—natural and environmentally friendly air fresheners. However, public knowledge about the utilization of orange peel is still limited. Vocational high school (SMK) students, as the young generation preparing to enter the workforce or become entrepreneurs, can play an important role in developing this innovation. Through education and training, SMK students can learn the process of making reed diffusers from orange peel, starting from essential oil extraction to product packaging. This not only hones technical skills and creativity but also opens up entrepreneurial opportunities. The utilization of orange peel for reed diffusers aligns with the principles of circular economy and sustainable development, which emphasize the efficient use of resources. By mastering these skills, SMK students can contribute to reducing organic waste while creating products with high economic value. This also supports the vision of vocational education to produce competent, creative, and competitive graduates. This community service activity was carried out at SMK Astra Mitra Purwodadi, located in Grobogan Regency. The aim of the program was to provide participants with knowledge on how to produce reed diffusers using orange peel as the main ingredient.